(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article talks about the emergence of the concept of travel journalism and its formation and development as a profession. This direction of journalism, formed in foreign countries, is also reflected in the mass media of Karakalpakstan. The article contains controversial discussions about the concept of travel journalism.